(untitled) (Bangladesh Journal of Botany, 2022)
Amaranthus lividus and Amaranthus tricolor were evaluated for their primary free radical scavenging, membrane stabilizing and thrombolytic potentials. The methanol crude extracts of these two species were partitioned into petroleum ether, dichloromethane and aqueous soluble fractions. Antioxidant potential of the extracts was evaluated through DPPH and H2O2 free radical scavenging assays, where the aqueous soluble fraction of A. lividus exhibited the highest activity (p < 0.05). Besides, the maximum level of total phenolics was quantified in the aqueous fraction of A. lividus. Higher level (p < 0.05) of flavonoids (> 70 mg of QE/g of extract) were measured in the aqueous, dichloromethane and crude methanol extracts of A. lividus. The membrane stabilizing (anti-inflammatory) potential of the extracts was studied by measuring the inhibition of hemolysis of RBC induced by hypotonic solution and heat. Considering the conditions of both assays, the aqueous extract of A. lividus showed potent membrane stabilizing activity (p < 0.05) indicating their primary antiinflammatory potential. Very mild thrombolytic activity was noticed for both plants compared to the standard. Furthermore, existence of some major phytochemicals, like alkaloids, steroids, triterpenes and quinones were also observed at various levels. This is the first time report of the comparative assessment of the above mentioned plant extracts so far. Bangladesh J. Bot. 51(1): 139-145, 2022 (March)